2011
DOI: 10.1111/j.1365-2621.2011.02603.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability of previously frozen ostrich Muscularis iliofibularis packaged under different modified atmospheric conditions

Abstract: This study investigated the aptness of modified atmospheric packaging (70:30, O 2 :CO 2 (O_MAP); 70:30, N 2 :CO 2 (N_MAP)) and traditional overwrap (control) for previously frozen ostrich steaks, stored at 4 ± 1°C for 10 days. The N_MAP showed the least oxidation, O_MAP the highest and the control moderate. The redness (CIE a*) decreased to 3.67 ± 0.83 by day 10 in the O_MAP, the N_MAP and control initially had lower values indicating slower oxidisation. The free carbonyl production was higher in the O_MAP tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 41 publications
3
26
0
3
Order By: Relevance
“…The difference in pH values found in our study is also reported by other researchers (e.g. Bingol & Ergun, 2011;Fernandez-Lopez, Sayas-Barbera, Munoz, Sendra, Navarro, & Perez-Alvarez, 2008;Leygonie, Britz, & Hoffman, 2011a;Seydim, Acton, Hall, & Dawson, 2006) and is probably related to the difference in chemical composition between the meat of two species, including lipids, minerals and amino acids and specially in compounds such as creatine, which is relatively high in ostrich meat (Azad & Atker, 2005). Muscle glycogen undergoes glycolysis, producing lactic acid, which promotes rapid pH drop.…”
Section: Phsupporting
confidence: 88%
“…The difference in pH values found in our study is also reported by other researchers (e.g. Bingol & Ergun, 2011;Fernandez-Lopez, Sayas-Barbera, Munoz, Sendra, Navarro, & Perez-Alvarez, 2008;Leygonie, Britz, & Hoffman, 2011a;Seydim, Acton, Hall, & Dawson, 2006) and is probably related to the difference in chemical composition between the meat of two species, including lipids, minerals and amino acids and specially in compounds such as creatine, which is relatively high in ostrich meat (Azad & Atker, 2005). Muscle glycogen undergoes glycolysis, producing lactic acid, which promotes rapid pH drop.…”
Section: Phsupporting
confidence: 88%
“…Leygonie et al [5] argue that given the proper freezing storage conditions, the pH of broiler chicken breast meat decreases with increasing storage duration, which is attributable to the loss of water with its associated soluble substances, the progressing process of glycogenolysis, and the accumulation of acidic products of ongoing transformational processes that are usually intensified during thaw processes [6]. Additionally, the process of protein denaturation may bring about the freeing of hydrogen ions [30]. e current study (Table 1) did not, however, indicate any impact of freezing storage duration on the pH of breast meat (p > 0.05).…”
Section: Journal Of Food Qualitymentioning
confidence: 99%
“…A further explanation relates to the deamination of proteins by microbial or enzymatic action, with the ensuing release of hydrogen atoms (Leygonie et al, 2011). However, pH has been seen to strongly increase when much longer ST (15 mo) is applied, due to further deamination of proteins, leading to high amount of total volatile nitrogen formation .…”
Section: Effect Of Storage Time (St) On Ph and L*a*b* Colour Of The Lmentioning
confidence: 99%